Pentingnya Etika Public Relations Melalui Media Sosial Mengenai Kasus Pelecehan Seksual Di KRL Commuter Line - Khisma Rahmitha Rivka Yani; Putri Nabila (Sadida Islamic Communications and Media Studies, 2021)
Social media is currently experiencing extraordinary growth and development. Public relations ethics is one form of communication that must be applied in social media. Communiter Line is the Twitter account of PT KAI Commuter in Indonesia. But unfortunately, the account is considered to violate public relations ethics in social media. This research is entitled "The Importance of Public Relations Ethics Through Social Media Regarding Sexual Harassment Cases on the KAI Commuter Line". The admin of the official Twitter account of PT KAI Commuter @CommuterLine had become a netizen conversation. The Twitter admin was judged to have made a mistake in responding to complaints of alleged sexual harassment from fellow KRL users. The purpose of this study was to analyze the application of Public Relations Ethics in cases of sexual harassment that occurred in KRL through the Twitter account @CommuterLine.